Evaluation of hydrogen separation performance of Ni-BaCe0.85Fe0.15O3-δ cermet membranes. Issue 8 (1st June 2019) - Zhuang, Libin; Li, Jiaqi; Xue, Jian; Jiang, Zhouyang; Wang, Haihui
Abstract: Adding metal phase as the electronic transport channels in mixed protonic and electronic conductors is an effective method to enhance the conductivity and hydrogen permeability. Ceramic-metal (cermet) Ni-BaCe0.85 Fe0.15 O3-δ (Ni-BCF8515) dual-phase membranes were successfully fabricated in this article, where BaCe0.85 Fe0.15 O3-δ (BCF8515) served as the protonic conductor and Ni acted as the electronic conductor. The hydrogen permeability of Ni-BCF8515 dual-phase membrane was improved apparently, reaching 0.325 mL min −1  cm −2 at 1000 °C, which is four times higher than that of the single phase BCF8515 membrane. Hydrogen permeability of Ni-BCF8515 dual-phase membrane under different hydration conditions was studied here. Moreover, Ni-BCF8515 dual-phase membrane showed stable hydrogen permeability under the reducing atmosphere for 50 h.